2017
DOI: 10.1016/j.fuel.2016.10.117
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effect of ozonation and electrochemical methods on oxidation and toxicity reduction: Phenol degradation

Abstract: h i g h l i g h t s O 3-EO enhances by 2.5 times the mineralization of phenol when compared to O 3 alone. O 3-EO reduces by half the time to achieve a phenol mineralization >90%. Ozonation alone fails on phenol mineralization and on diminishing toxicity. Toxicity onto Latuca sativa is only eliminated by the coupled treatment (O 3-EO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…The appearance of intermediate compounds that are also being oxidized by hydroxyl radicals In Equation ( 9), M is an electroactive site of BDD anode where the hydroxyl radicals are formed by the anodic oxidation of water (Equation ( 10)) [43], φ, γ, δ and n e are stoichiometric coefficients. Equation ( 9) is the global mineralization reaction:…”
Section: Kinetics Of Ibu Mineralizationmentioning
confidence: 99%
“…The appearance of intermediate compounds that are also being oxidized by hydroxyl radicals In Equation ( 9), M is an electroactive site of BDD anode where the hydroxyl radicals are formed by the anodic oxidation of water (Equation ( 10)) [43], φ, γ, δ and n e are stoichiometric coefficients. Equation ( 9) is the global mineralization reaction:…”
Section: Kinetics Of Ibu Mineralizationmentioning
confidence: 99%
“…Ozonation (OZ) is a ‘quasi’ AOP that has one of the longest histories of use and research, reaching far back in the 20th century. A considerable amount of work has been reported so far on the removal of phenol (PHN) [ 16 , 17 , 18 , 19 , 20 ], 2,4-dichlorophenol (DCP) [ 18 , 21 , 22 ] and pentachlorophenol (PCP) [ 22 , 23 , 24 , 25 ], some reviewed, for example, by Pera-Titus et al [ 12 ] Studies in majority concluded that OZ exhibits high effectivity in removal of target phenol and CPs by progressive formation of multiple C–O and C=O bonds before or after destruction of aromatic ring, as well as cleavage of labile C–Cl, C–H, and C–C bonds. This is possible through molecular or radical mechanism [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the application of electrochemical technologies, it is of great importance to reduce the treatment time and optimize the operating conditions in order to achieve a good result of removal that represents a simple and low cost treatment. This has motivated coupling electrochemical methods with other treatments, such as: electro‐oxidation/ozonation,, direct UV‐C photolysis, UV‐C/H 2 O 2 and UV‐A/TiO 2 , ozone/hydrogen peroxide (O 3 /H 2 O 2 ), ultrasonic, etc. Preliminary investigations of Brillas using O 2 ‐diffusion cathode and Oturan group using carbon felt cathode with regard to the in‐situ H 2 O 2 formation during EO, taking advantage of the cathodic O 2 reduction, report the synergic effect of this oxidant .…”
Section: Introductionmentioning
confidence: 99%